Typography essentials : 100 design principles for working with type - Saltz, Ina (Beverly, MA : Rockport Publishers, an imprint of The Quarto Group, 2019)
Typography Essentials: 100 Design Principles for Working with Type is a practical, hands-on resource that distills and organizes the many complex issues surrounding the effective use of typography. An essential reference for designers since 2009, Typography Essentials is now completely refreshed with updated text, new graphics and photos, and a whole new look
First published in 2009
Includes bibliographical references
Includes index
1 10
Keywords: Graphic design (Typography); Type and type-founding